2022
DOI: 10.3897/bdj.10.e78666
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of Oxytropis DC. (Fabaceae) species in Asian Russia

Abstract: The dataset providing information on the geographic distribution of Oxytropis species on the territory of Asian Russia is discussed. The data were extracted from different sources including prominent floras and check-lists, Red Data books, published research on congeneric species and authors’ field observations and mainly cover less-studied, remote regions of Russia. The dataset should be of value to applied, basic and theoretical plant biologists and ecologists interested in the Oxytropis species. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Among our outgroups, we sampled 71 species of Oxytropis, a monophyletic closely related segregate of Astragalus more prevalent in the Arctic (Meyers, 2012;Sandanov et al, 2022) that has been studied previously using small numbers of chloroplast and nuclear ribosomal markers (Archambault and Strömvik, 2012;Meyers, 2012;Kholina et al, 2016Kholina et al, , 2020Tekpinar et al, 2016a;b), as well as phylogenomic data to a limited extent (Shahi Shavvon et al, 2017). Biogeography of the Oxytropis species of the Americas was investigated by Archambault and Strömvik (2012) and Tekpinar et al (2016b); both studies suggested multiple dispersals to the Americas from Eurasia, but were limited by very little nucleotide variation and were unable to target specifically the origin of this dispersal.…”
Section: Astragalus Oxytropis and Astragalean Clade Relationships-mos...mentioning
confidence: 99%
“…Among our outgroups, we sampled 71 species of Oxytropis, a monophyletic closely related segregate of Astragalus more prevalent in the Arctic (Meyers, 2012;Sandanov et al, 2022) that has been studied previously using small numbers of chloroplast and nuclear ribosomal markers (Archambault and Strömvik, 2012;Meyers, 2012;Kholina et al, 2016Kholina et al, , 2020Tekpinar et al, 2016a;b), as well as phylogenomic data to a limited extent (Shahi Shavvon et al, 2017). Biogeography of the Oxytropis species of the Americas was investigated by Archambault and Strömvik (2012) and Tekpinar et al (2016b); both studies suggested multiple dispersals to the Americas from Eurasia, but were limited by very little nucleotide variation and were unable to target specifically the origin of this dispersal.…”
Section: Astragalus Oxytropis and Astragalean Clade Relationships-mos...mentioning
confidence: 99%
“…Among our outgroups, we sampled 71 species of Oxytropis, a monophyletic segregate of Astragalus more prevalent in the Arctic (Meyers, 2012;Sandanov et al, 2022) that has been studied previously using small numbers of chloroplast and nuclear ribosomal markers (Archambault and Strömvik, 2012;Meyers, 2012;Kholina et al, 2016Kholina et al, , 2020Tekpinar et al, 2016a, b) and to a limited extent, phylogenomic data (Shahi Shavvon et al, 2017). Biogeography of the Oxytropis species of the Americas was investigated by Archambault and Strömvik (2012) and Tekpinar et al (2016b).…”
Section: Astragalus Oxytropis and Astragalean Clade Relationshipsmentioning
confidence: 99%